Colour forecasting. Issue 1 (2nd January 2019) - Cassidy, Tracy Diane
Abstract: The underlying principles of colour forecasting now have a history spanning a full century. This issue of Textile Progress is somewhat timely as the challenges that industry face now differ from those of the twentieth century, in particular, the increased need to address sustainability and the increased competiveness of the global marketplace. This Textile Progress provides an overview of the historical context drawing out the importance of the role of colour forecasting in the fashion and textile industries. It provides a detailed analysis of the more-recently established and establishing trend forecasting methods with a view to thinking more innovatively about the potential of colour forecasting. It investigates the effects and impact of colour and trend forecasting with a particular focus on the consequences of the process and system on business, on consumers and on the environment. In reviewing the developments in colour forecasting, we begin with the subjective techniques highlighting the strengths and weaknesses of the approaches. The more-objective characteristics that have emerged from new developments and new thinking provide a focus on the potential for greater accuracy in colour forecasting. This issue of Textile Progress explains how and why colour forecasting is an essential component of the business of making and selling fashion garments, through merchandising, retailing and fashion marketing, as well as being important in fashion design and product development processes. Developments affecting the design of colour forecasting systems are shown to draw on marketing theory, though without much consideration for the human-business interface, specifically, colour preferences, colour psychology and cultural meanings of colour. The overall aim of this Textile Progress is to assist an understanding of the colour forecasting process and its contribution to the larger trend forecasting system, and to highlight the challenges the colour forecasting sector faces for a twenty-first century fashion-business strategy. Attention is paid to the colour forecasting process and forecasting as a system, including its application in the design process and skills acquisition. The more-recently established trend forecasting methods are critically analysed, as are previously unpublished contributions to knowledge through original sets of primary research data, and finally potential improvements are suggested.